2018
DOI: 10.1007/s12035-017-0863-1
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Novel Object Recognition Memory and Brain Insulin Signaling in Fructose- but Not Glucose-Drinking Female Rats

Abstract: Excessive sugar intake has been related to cognitive alterations, but it remains unclear whether these effects are related exclusively to increased energy intake, and the molecular mechanisms involved are not fully understood. We supplemented Sprague-Dawley female rats with 10% w/v fructose in drinking water or with isocaloric glucose solution for 7 months. Cognitive function was assessed through the Morris water maze (MWM) and the novel object recognition (NOR) tests. Plasma parameters and protein/mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 66 publications
11
44
0
Order By: Relevance
“…Also, it has been described that increased slow oscillatory activity, a hallmark of NREM, is associated with better performance in different tasks of episodic memory and novel objects recognition [40]. It has been described that chronic intake of 10% fructose in drinking water induces impairment of spatial memory and novel object recognition memory [15,20]. Our results show that fructose diet significantly reduces the total time spent in NREM sleep.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Also, it has been described that increased slow oscillatory activity, a hallmark of NREM, is associated with better performance in different tasks of episodic memory and novel objects recognition [40]. It has been described that chronic intake of 10% fructose in drinking water induces impairment of spatial memory and novel object recognition memory [15,20]. Our results show that fructose diet significantly reduces the total time spent in NREM sleep.…”
Section: Discussionsupporting
confidence: 63%
“…Also, the report of Yin et al [15] showed that rats receiving a lower concentration (10% fructose solution in drinking water) exhibited a significant increase in the escape latency of the Morris water maze test. More recently, a study analyzed other cognitive parameters and showed that fructose supplementation induces an impairment of the novel object recognition memory [20].…”
Section: Introductionmentioning
confidence: 99%
“…Brain metabolic remodeling appears to occur precociously without a concurrent increase in overall energy intake and seems consequently to be linked to fructose itself. These disturbances should be more explored to elucidate deleterious long-term outcomes, such as memory impairments, as recently proposed ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sleep restriction for 6-h during four days selectively impaired spatial learning and decreased the number of mitotic cells in the hippocampus [ 42 ]. Interestingly, Inostroza et al reported that short periods (80 min) of sleep restriction are enough to decline the consolidation and retrieval of spatial and temporal memories in a novel-object recognition task [ 43 ].It has been described that chronic intake of 10% fructose in drinking water induces impairment of spatial memory and novel object recognition memory [ 15 , 20 ]. Our results show that fructose diet significantly reduces the total time spent in NREM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the report of Yin et al [ 15 ] showed that rats receiving a lower concentration (10% fructose solution in drinking water) exhibited a significant increase in the escape latency in the Morris water maze test. More recently, a study analyzed other cognitive parameters and showed that fructose supplementation induces an impairment of the novel object recognition memory [ 20 ].…”
Section: Introductionmentioning
confidence: 99%